Packet Media Streaming with Imprecise Rate Estimation - Dan Jurca; Pascal Frossard (Advances in Multimedia)
We address the problem of delay-constrained streaming of multimedia packets over dynamic bandwidth channels. Efficient streaming solutions generally rely on the knowledge of the channel bandwidth, in order to select the media packets to be transmitted, according to their sending time. However, the streaming server usually cannot have a perfect knowledge of the channel bandwidth, and important packets may be lost due to late arrival, if the scheduling is based on an over-estimated bandwidth. Robust media streaming techniques should take into account the mismatch between the values of the actual channel bandwidth and its estimation at the server. We address this rate prediction mismatch by media scheduling with a conservative delay, which provides a safety margin for the packet delivery, even in the presence of unpredicted bandwidth variations. We formulate an optimization problem whose goal is to obtain the optimal value for the conservative delay to be used in the scheduling process, given the network model and the actual playback delay imposed by the client. We eventually propose a simple alternative to the computation of the scheduling delay, which is effective in real-time streaming scenarios. Our streaming method proves to be robust against channel prediction errors, and performs better than other robustness mechanisms based on frame reordering strategies.